Sigil software based e-module validation for class VII students on data presentation material - Melisha Apriliani; Ainil Mardiyah; Ratulani Juwita (UNION : Jurnal Ilmiah Pendidikan Matematika, 2023)
The purpose of this research is to produce an Android-based e-Module using Sigil software that is valid and practical for Class VIIA Data Presentation at SMP N 24 Padang that is valid and practical so that it can be used as a source of learning mathematics, especially data presentation material. The type of research used is development research. This research uses the Plomp model. The stages used in this development model are only stages 1 to stage 2, namely the initial investigation stage, the prototyping phase which concurrently tests the validity and practicality. The research instrument used is a validation questionnaire, a one-on-one test questionnaire that is useful for seeing the practicality of e-Modules by teachers, small group test questionnaires that are useful for seeing the practicality of e-Modules by students and interview guidelines. Based on the validator's assessment, the results of the validity of the Android-based e-Modul using the Sigil software were 90.33% with a very valid category. The final value of practicality with the teacher obtained a final score of 80% in the practical category. The final value of practicality with students was obtained 88.61% with a very practical category. Based on the results of the study, it can be concluded that the Android-based e-Module using Sigil software in Data Presentation in class VIIA SMP N 24 Padang is valid and practical for use by teachers and students.